Advances in cotton science: botany, production, and crop improvement - Maiti, R. K.; Aruna Kumari, C. H., (ed.); Huda, Abul Kalam Samsul, (ed.); Mandal, Debashis, (ed.); Begum, Sameena, (ed.) (Ontario Apple academic press, 2021)
"Cotton is one of the most important fiber and cash crops throughout the world, and it plays a dominant role in the industrial and agricultural economies of many countries. This volume, Advances in Cotton Science: Botany, Production, and Crop Improvement, is a rich resource of information on the cultivation and production of cotton. It provides an overview of its origin and evolution, and its physiological basis and characterization, and goes on to discuss methods of cultivation, biotic stresses, harvesting and postharvest technology, and new research on breeding and biotechnology. The authors take an interdisciplinary approach, providing a multi-pronged approach to information necessary to increase cotton productivity to meet the world's growing demands. The volume answers the need to understand the roles of cotton, the nature of the crop, and advancements in research for best cultivation methods, effective utilization of resources, and operations for achieving higher yields, thus achieving higher productivity. The volume will be immensely helpful for growers, students, academicians, teaching faculty, and other professionals in the field to gain knowledge and understanding of the crop"--
Keywords: Cotton; Cotton growing